Rationale and Formulation of the Featured Program of Hifdzul Qur'an at Junior High School - Muslimah; Anwar, Khairil; Ahmad, Sabarudin; Hafifah, Wafiq (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This research aims to analyze the rationale and formulation of a featured program, namely Hafidz Quran, which is implemented by educational institutions, especially at Muhammadiyah Sukamara Junior High School. The research was qualitative, which did not use statistical formulas in processing and analyzing data but was described naturally as it was. The study found that the formulation and rationale for the featured program of Hifdzul Qur'an at Muhammadiyah Sukamara Junior High School is the juridical formulation consisting of Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System and Muhammadiyah Central Leadership Guidelines Number 01/PED/I.0/B /2018 concerning Muhammadiyah Primary and Secondary Education. The religious formulation is based on the guidance of the Quran and Hadith, which are the basic needs of managers and society. Apart from being a continuation program for tahfiz from kindergarten and elementary school, this program is also a necessity for schools and the community in building the nation's life more intelligently.